Histochemistry - Zhou, Jinsong, 1970- (De Gruyter, 2017)
This book systematically illustrates theories and technologies in Histochemistry, including different kinds of enzymes, immunohistochemistry, polymerase chain reaction, related electron microscopic cytochemical techniques as well as the quantitative assay metrology. Abundant experiments as well as vivid images are demonstrated, making the book an essential reference for both graduate students and researchers in biochemistry.
Keywords: Histochemistry.; Diagnostic immunohistochemistry.; Histocytochemistry -- methods; Immunohistochemistry -- methods; Biochemical Phenomena; Histocytochemistry; Histochimie.; Immunocytochimie clinique.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Diagnostic immunohistochemistry; Histochemistry; Histochemie; (Produktform)Electronic book text; (Zielgruppe)Fachhochschul-/Hochschulausbildung; (BISAC Subject Heading)SCI010000; (BISAC Subject Heading)SCI013020: SCI013020 SCIENCE / Chemistry / Clinical; (BISAC Subject Heading)SCI007000: SCI007000 SCIENCE / Life Sciences / Biochemistry; TB: Textbook; (VLB-WN)9675; (Produktrabattgruppe)PN: nicht rabattbeschränkt/Sortimentstitel